Comparative study of non-invasive blood pressure measurement methods in elderly people - Fabián, Vratislav; Janouch, Martin; Nováková, Lenka; Štěpánková, Olga (Conference proceedings ... Annual International Conference of the IEEE Engineering in Medicine and Biology Society, 2007)
Results obtained by the modern automatic blood pressure (BP) monitors using oscillometric method [5] are highly dependent on conditions of cardiovascular system of the monitored person. Especially, with people who suffer from cardiovascular diseases (e.g. atherosclerosis) the resulting values differ significantly from those measured by the traditional auscultation method. A reasonable solution for improvement of quality of oscillometric method could be a sophisticated intelligent BP measuring system which applies for evaluation of BP more complex approach taking into account the monitored person's condition of patient cardiovascular system (CS) i.e. the hemodynamic parameters of CS (e.g. heart rate, stroke volume, total peripheral resistance, systemic arterial compliance, pulse wave velocity, augmentation index etc.). Such a system has to be based on appropriate models of the considered diseases which are validated on real life data. For that purpose, we have started to build a database of real-life oscillometric pulsations waveforms (OPW) complemented by the values of "auscultation" blood pressure measurements and additional relevant information about the considered patients (age, sex, etc.) as well as their diagnosis. This data collection requires a special HW device for measurement of the OPW--we have developed such a device and it has been validated in Czech Certified Metrological Centre. Our OPW monitor is connected through the T-pieces and tubes to the cuff, mercury sphygmomanometer and automatic "oscillometric" blood pressure monitor.
Keywords: financování organizované; Blood Pressure Monitors; Hemodynamics; hemodynamika; lidé; triáda sportovkyň; Female Athlete Triad Syndrome; Blood Pressure Monitoring, Ambulatory; databáze faktografické; Aged, 80 and over; monitory krevního tlaku; Financing, Organized; Male; Cardiovascular Diseases; Aged; ambulantní monitorování krevního tlaku; kardiovaskulární nemoci; Databases, Factual; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; Humans